The clinical utility of single-balloon enteroscopy: a single-center experience of 172 procedures - Upchurch, Bennie R.; Sanaka, Madhusudhan R.; Lopez, Ana Rocio; Vargo, John J. (Gastrointestinal endoscopy, 2010)
Single-balloon enteroscopy (SBE) is a novel endoscopic technique designed to evaluate and treat small-bowel disease. Although there is substantial literature addressing double-balloon enteroscopy and its impact on the diagnosis and management of small-bowel disease, there are limited data available on the clinical utility of SBE. To evaluate the clinical utility and diagnostic impact of SBE in a large cohort of patients at a single tertiary center. Single-center, retrospective study. Digestive Disease Institute, Cleveland Clinic, Cleveland, Ohio. A total of 161 patients were referred for SBE from January 2006 to August 2008. Demographic, clinical, procedural, and outcome data were collected and analyzed. A total of 161 patients underwent a total of 172 procedures. Antegrade and retrograde approaches were used in 83% and 17% of subjects, respectively. The average insertion depth using the antegrade approach was 132 cm beyond the ligament of Treitz (range 20-400 cm). The average insertion depth using the retrograde approach was 73 cm above the ileocecal valve (range 10-160 cm). The average procedure time was 40 minutes overall, 38 minutes (range 12-90) antegrade and 48 minutes (range 28-89) retrograde. Fluoroscopy was used in 20 cases (12%). Diagnostic yield was 58% (99/172); 42% (72/172) were therapeutic cases. There were no significant complications. Single-center, retrospective study. SBE demonstrated a high diagnostic yield and frequently provided useful therapeutic intervention. It seems to be a safe and effective method for performing deep enteroscopy.